Managing taro leaf blight - Arutselvan, R; Kumar, H Kesava; More, Sanket J; Sangeetha, B G (Indian Horticulture, 2019)
Leaf blight is observed in severe form in areas having high relative humidity and frequent rainfall, whereas warmer areas having little rainfall and relative humidity are comparatively free from this disease. The disease begins as purple-brown water-soaked lesions on the leaf. A clear yellow liquid oozes from the lesions. These lesions then enlarge, join together and eventually destroy the entire lamina in two weeks. Free water collecting on older leaves, as well as high temperature and high humidity are conducive to onset and spread of the disease and germination of the spores. The disease can spread from plant to plant by wind and splashing rain. Spores survive in planting material for three or more weeks. Thus, infected planting material is one common means of spreading the disease over long distances and from season to season.